Ecogeographical patterns of morphological variation in pygmy shrews Sorex minutus (Soricomorpha: Soricinae) within a phylogeographical and continental‐and‐island framework. (14th July 2016) - Vega, Rodrigo; Mcdevitt, Allan D.; Kryštufek, Boris; Searle, Jeremy B.
Abstract : Ecogeographical patterns of morphological variation were studied in the Eurasian pygmy shrew Sorex minutus aiming to understand the species' morphological diversity in a continental and island setting, and within the context of previous detailed phylogeographical studies. In total, 568 mandibles and 377 skulls of S. minutus from continental and island populations from Europe and Atlantic islands were examined using a geometric morphometrics approach, and the general relationships of mandible and skull size and shape with geographical and environmental variables were studied. Samples were then pooled into predefined geographical groups to evaluate the morphological differences among them using analyses of variance, aiming to contrast the morphological and genetic relationships based on morphological and genetic distances and ancestral state reconstructions, as well as assess the correlations of morphological, genetic, and geographical distances with Mantel tests. We found significant relationships of mandible size with geographical and environmental variables, fitting the converse Bergmann's rule; however, for skull size, this was less evident. Continental groups of S. minutus could not readily be differentiated from each other by shape. Most island groups of S. minutus were easily discriminated from the continental groups by being larger, indicative of an island effect. Moreover, morphological and genetic distances differed substantially and, again, island groups were distinctive morphologically. Morphological and geographical distances were significantly correlated, although this was not the case for morphological and genetic distances, indicating that morphological variation does not reflect genetic subdivision in S. minutus . Our analyses showed that environmental variables and insularity had important effects on the morphological differentiation of S. minutus .